'I don't go to the gigs to go to the gigs – I don't give a shit about the gigs!': Exploring gig attendance and older punk women. (1st June 2019) - Way, Laura
This article considers gig attendance amongst a sample of twenty-two older punk women. A feminist methodology was employed, with qualitative data collected through semi-structured interviewing with seventeen older punk women, and an additional five women answering questions by e-mail correspondence. With the majority of the research sample attending gigs on a regular basis, it could be assumed that this meant music was a significance part of 'doing' punk but this was realized to be quite a simplistic assumption. The article will consider this in more detail through discussing two key questions: What are the key reasons and motivators behind older punk women attending gigs? What barriers do these women face when it comes to gig attendance?